Implementasi Program Edukasi Anti-Bullying dalam Meningkatkan Pemahaman Siswa Sekolah Dasar Tentang Pencegahan Perundungan di SD Negeri No. 105361 Desa Lubuk Cemara - Irwan S; Widya Nur’aini; Nurmawaty Hasugian; Ikhsan Prasetyo; Safrina; Khairunissa (Jurnal Pendidikan Indonesia, 2026)
Bullying still happens in many elementary schools. Victims can experience psychological problems, have trouble socializing, and see their grades drop. Because students don’t really understand what bullying is or how to prevent it, they often think such behavior is normal in everyday interactions. Observations at an elementary school in Lubuk Cemara Village show that some students still don’t fully understand the definition, types, impacts, and ways to prevent bullying. Therefore, educational activities are needed as a preventive measure to increase students’ knowledge and awareness so that a safe and respectful school environment can be created. This community service activity aims to educate students about preventing bullying through an anti-bullying socialization program. The methods used included field observation, problem identification, preparation of educational materials, and conducting outreach through lectures, discussions, and Q&A sessions. The activities ran smoothly and received positive responses from both students and the school. Students seemed enthusiastic about the material, actively participated in discussions, and were able to recognize various forms of bullying as well as the importance of mutual respect. This program is hoped to help develop students’ characters to be empathetic and respectful towards others, creating a safe, comfortable, and bullying-free school environment